The 6th grade students' view in understanding mathematics through reading mathematics textbook. (March 2020) - Turidho, A; Maharani, Y; Darmawijoyo,
Abstract: This research aims to describe students' views in understanding mathematics by reading a mathematics textbook. The subjects of this research were 6 students on grade VI at Singapore International School (SIS) Palembang. This is descriptive research. The research instruments were interviews and questionnaires. Based on the results, 50% of students read a mathematics textbook by reading definitions or rules, learning examples of the problems and doing exercises. And 50% of students read a mathematics textbook by learning examples of the problems, reading definitions or rules and doing exercises. In understanding mathematics, 16.7% of students felt understood mathematics textbook after understood the definitions or rules, 33.3% of students felt understood mathematics textbook after doing the mathematics problems, 33.3% of students felt understood mathematics textbook after doing exercises and 16.7% of students felt understood mathematics textbook after doing mathematics problems and understanding definitions or rules.